The culture of design. - Julier, Guy, ....- (Los Angeles : SAGE, 2010)
'Julier provides an important contemporary account of how design disciplines act and interact in the world.. an important resource for the student of design. perfection as a cultural studies text' - European Journal of Cultural Studies Aimed at students of design studies, design history, cultural studies and sociology, The Culture of Design, offers a unique overview of design practice in contemporary culture and society. Drawing on a range of theoretical perspectives, Julier nevertheless foregrounds the everyday business and professional context in which designers work. The second edition of The Culture of Design, has been thoroughly revised and updated, and contains new case studies, including one on the i-pod. In addition, the book now has an extended final chapter which looks at the links between design and business studies and how the creative industries function in the context of contemporary audit culture.